Refining the flesch reading ease formula for intermediate and high-intermediate ESL learners / Anealka Aziz Hussin - Aziz Hussin, Anealka (Penerbit UiTM (UiTM Press), 2015)
ESL instructors tend to rely on their judgment in estimating the difficulty level of reading passages for their learners. This commonsense method, despite being drawn from experience, gut feeling and intrinsic knowledge of the learners' ability, is neither efficient nor objective. A more objective method is available such as using readability formulas to estimate the difficulty level of the passages. One of the highly reliable readability formulas which have been validated to be used in an ESL/EFL context is the Flesch Reading Ease (FRE) formula. The FRE formula has a difficulty scale that ranges from 0 (the least difficult) to 100 (the most difficult), which is rather broad and general. Therefore, it was the intention of this study to refine the FRE difficulty scale for the use of a specific group of learners and identify additional predictors of passage difficulty to enhance the ability of the formula in estimating the difficulty level of reading passages. To do that, the study replicated Vogel and Washburne's (1928) process of developing modern readability formula.